Pendampingan Kader dalam Deteksi Dini Mental Health Disorders pada Anak di Posyandu Ngadi Asih Joglo Banjarsari Surakarta - Darah Ifalahma; Fitriana Yuni Permana Sari; Adisty Amalya Putri Handayani; Nurlaila Siti Zamrina (Jurnal Kemitraan Masyarakat, 2024)
Ngadi Asih Posyandu is one of the Posyandu in the Joglo Village area, Banjarsari District, Surakarta City and is included in the UPT Targeted Area of ​​the Gambirsari Health Center, Surakarta. Ngadi Asih Posyandu activities are routinely held every month on the first Saturday of the week. The number of babies and toddlers in the posyandu is approximately 50 children, and the number of cadres on duty is 20 people. The priority problem found at Posyandu Ngadi Asih Surakarta is that early detection of Mental Health Disorders in children has not been carried out due to limited knowledge and skills of cadres. Apart from that, cadres do not understand Mental Health Disorders in children, and do not have an early detection instrument, the Behavioral and Emotional Problems Questionnaire (KMPE). The focus of this program is training cadres on early detection of Mental Health Disorders or mental emotional and behavioral problems using the Behavioral and Emotional Problems Questionnaire (KMPE), counseling cadres about Mental Health Disorders in children, as well as providing assistance to cadres in post-training posyandu activities. The method used consists of 6 stages, namely Preparation, Apperception, Training, Post-training assistance, Evaluation and Termination of activity results. The results of cadre assistance activities in early detection of mental health disorders in children at the Ngadi Asih Posyandu went well. There was an increase in cadre knowledge by 35% and cadre skills in the good category by 60%. Cadres are committed to carrying out and implementing the results of activities in each posyandu agenda. The PkM team is also willing to provide consultations at any time if cadres need advice or assistance.